Tourism and territorial growth determinants in insular regions: A comparison with mainland regions for some European countries (2008–2019). Issue 6 (5th September 2022) - Mazzola, Fabio; Pizzuto, Pietro; Ruggieri, Giovanni
Abstract: The article investigates the different growth patterns of islands and mainland regions by looking at their tourism and territorial characteristics differences. We considered per capita income and employment growth patterns in a panel data model focused on 74 regions in seven European countries from 2008 to 2019. The results show how the importance of some growth factors, especially those related to tourism and environmental sustainability, varies between islands and mainland regions. The article suggests specific policy implications for island regions in line with the European Union guidelines. Our findings support the need to pursue different approaches to sustain growth in islands and mainland regions, particularly for the tourism industry. Resumen: Este artículo investiga las diferentes pautas de crecimiento de las islas y las regiones continentales mediante un examen de sus diferencias en materia de turismo y características territoriales. Se consideraron los patrones de crecimiento de la renta per cápita y del empleo en un modelo de datos de panel basado en 74 regiones de siete países europeos entre 2008 y 2019. Los resultados muestran la variación de la importancia de algunos factores de crecimiento, especialmente los relacionados con el turismo y la sostenibilidad medioambiental, entre las islas y las regiones continentales. El artículo sugiere implicaciones políticas específicas para las regiones insulares de acuerdo con las directrices de la Unión Europea. Las conclusiones respaldan la necesidad de aplicar distintos enfoques para mantener el crecimiento en las islas y en las regiones continentales, en particular para la industria del turismo. 抄録: 本稿では、離島と本土地域の成長パターンの違いを、観光と土地の特性の違いから検討する。2008 2019年まで欧州の7カ国の74地域のパネル・データ・モデルにおいて、一人当たりの所得と雇用成長のパターンを考察した。結果から、いくつかの成長要因、特に観光と環境の持続可能性に関連するものの重要性が、離島と本土地域とでどう違うかが示された。本稿は、EUのガイドラインに沿った、島嶼地域に対する具体的な政策的含意を示唆するものである。本研究の知見は、成長の維持、特に観光産業のためには、離島と本土地域とで異なるアプローチを追求する必要性を支持するものである。